Contracting out of Access to Justice: Enforcement of Forum-Selection Clauses in Consumer Contracts - Pavlović, Marina (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2016)
Forum-selection agreements in consumer contracts nominate by default the business’s home jurisdiction to resolve disputes and thus directly impact a consumer’s ability not only to access courts, but also to obtain access to substantive justice. It has been argued that courts should consider enforcing jurisdiction clauses in consumer contracts with “greater scrutiny” because of their inherent power imbalance. To examine how the courts approach forum-selection clauses in consumer contracts, this article analyzed all reported consumer cases involving forum-selection agreements in Canadian common law jurisdictions between 1995 and 2016. The analysis of these cases shows that the courts have failed to exercise the greater scrutiny that was called for. In light of the analysis of the surveyed cases, this article argues that the rules for enforcing forum-selection clauses in consumer contracts ought to be recalibrated to reflect the power dynamics of consumer relationships, the ubiquity of standard-form contracts, and their effect on consumers’ ability to obtain redress. This article proposes two suggestions for reform: legislative intervention to invalidate forum-selection clauses in consumer agreements, and reframing and recalibrating the common law strong-cause test for the enforcement of forum-selection clauses in consumer transactions.